Sourcing2Equal Kenya : Barriers and Approaches to Increase Access to Markets for Women-Owned Businesses - International Finance Corporation (Washington, DC, 2022)
Small and medium enterprises (SMEs) make up a large part of Kenya’s economy, accounting for approximately 98 percent of all businesses. SMEs are found in all sectors of the economy, they are estimated to contribute about 80 percent of total employment in Kenya, and they play a central role in Kenya’s economic growth. Women’s ownership of formal SMEs is low, comprising only about one third of registered SMEs. Women-owned and led SMEs (WSMEs) face structural barriers in growing their businesses due to their limited access to: finance, business networks and connections, and market information. Consequently, these barriers limit WSMEs’ ability to access new markets, such as procurement contracts with private sector Buyers. In 2020, IFC established Sourcing2Equal, a global program that aims to connect 5,000 WSMEs to private procurement opportunities by 2023. The first project under the program is in Kenya. This report examines the barriers that Kenyan SMEs face in accessing private procurement contracts, and if there are differences based on whether companies are owned by women, men, or owned jointly by women and men. Analysis of survey data from 571 SMEs, and interviews with 14 corporate Buyers in Kenya, provide unique data on gender gaps in the participation of SMEs in corporate supply chains, and it reveals emerging practices that are aiming to increase the procurement of goods and services from WSMEs. The sample of formally registered SMEs was selected from a defined population in business membership organizations’ databases, rather than from a national census dataset. Due to the potential risk of homogeneity in the sample, the statistically significant results of this study should not be assumed to be representative of the whole SME population